A20 (TNFAIP3) alleviates CVB3-induced myocarditis via inhibiting NF-κB signaling. - Jun Gui (Public Library of Science (PLoS), 2012)
Background Viral myocarditis, which is most prevalently caused by Coxsackievirus B3 (CVB3) infection, is a serious clinical condition characterized by cardiac inflammation. However, efficient therapies targeting inflammation are still lacking and much needed. A20, also known as tumor necrosis factor alpha induced protein 3 (TNFAIP3) is a key negative regulator of inflammation. But whether A20 may affect cardiac inflammation during acute viral myocarditis remains to be elucidated. The aim of this study was to investigate the potential protective effect of A20 on CVB3-induced myocarditis. Methodology/principal findings Mice were intraperitoneally inoculated with CVB3 to establish acute viral myocarditis model. We found that the expression of pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6 and monocyte chemotactic protein-1 (MCP-1) were markedly and persistently increased during the progression of CVB3-induced myocarditis, and positively correlated with the disease severity. Notably, intravenous injection in vivo with adenovirus expressed A20 (Ad-A20) remarkably reduced CVB3-induced pro-inflammatory cytokines production and alleviated the severity of myocarditis. Further, we observed that nuclear factor-kappaB (NF-κB) signaling which mediates inflammatory response was significantly inhibited in CVB3-infected mice with Ad-A20 treatment. Finally, we revealed that A20 was required to inhibit CVB3-induced NF-κB signaling by restricting TNF receptor associated factor 6 (TRAF6) ubiquitylation. Conclusion/significance This study demonstrates the protective role of A20 against CVB3-induced myocarditis, which may provide a new therapeutic strategy for the treatment of viral myocarditis.